Kuala Lumpur urban biodiversity: a relation between urban-birds and people - Hj. Baharuddin, Zainul Mukrim; Rusli, Fatin Nadia; Othman, Rashidi (2014)
Due to the growing human population, numerous developments are needed until today. Thus, it caused massive changes to the landscape from natural to built environment. Consequently, the earth confronted critical issues on protection and restoration of biodiversity. The impact of urbanization on biodiversity is concerned on the relationship between biodiversity and urban ecosystem. The aim of this paper is to investigate abundance of urban biodiversity and its benefits to the urban community. The triangulation methodology address three step approaches biodiversity observation, atmospheric measurement and human dimension. However, this study will present the abundance of bird observation in year 2010 and 2014. 11 species of birds were identified. The highest number of birds recorded is (Acridotheres tritis/common myna (n=56) in 2010 and (n=19) in 2014. It is recorded that there are decreasing number of birds species such as Zebra Dove and Magpie Robin. There are new species identified in 2014 the Black Crowned Night Heron which are rarely found in urban area. The study presents and empirical survey on bird species. The declining of green space in urban affected the bird species population. It is suggested that bird conservation in urban context should be emphasized. It could improve the ecosystem services as well as health and well-being benefits